Fresno County Bar Association and American Civil Liberties Union Celebrate the Constitution at Fresno City College - Watkins, Howard::::::::: (1988)
Howard Watkins holding up Women's International League for Peace and Freedom bus placard reading: "Why is this the only job our government has to offer 18 year olds? Think Before You Register For The Draft"